REMITTANCES, HUMAN CAPITAL, AND LOCAL RESILIENCE: CROSS-BORDER MIGRATION DYNAMICS IN THE INDONESIA–MALAYSIA BORDER - Syahrudin, Husni; Ulfah, Maria (STKIP Persada Khatulistiwa Sintang, 2025)
International labor migration plays a crucial role in shaping socio-economic development in emerging economies, particularly through remittances that enhance household welfare and social resilience. This study explores how remittance utilization and human resource development (HRD) interact to influence community resilience in the Indonesia–Malaysia border area of Aruk, Sambas District. Using a qualitative descriptive approach through in-depth interviews, observation, and documentation, the study analyzes the economic and social dynamics of migration among border communities. The findings reveal that migration is primarily driven by limited employment opportunities, wage disparities, and inadequate vocational training. While remittances significantly improve family income and education, their long-term contribution depends on productive investment and skills development. The study highlights the need for inclusive HRD strategies that align education and training programs with labor market demands to strengthen local competitiveness. Integrating digital literacy and entrepreneurship training is essential to reduce dependency on cross-border labor migration and promote sustainable livelihoods. These findings provide a framework for policymakers to design targeted interventions for human capital strengthening in border regions.